Potential Role of Propolis Flavonoid on Malondialdehyde and Superoxide Dismutase Levels on Endometriosis - Mayasari, Citra Krisna; Retno Gunarti, Dwirini; Octovia, Lily Indriani (Journal La Medihealtico, 2024)
Endometriosis is a prevalent gynecological condition that affects around 10% of women within the reproductive age group globally. Recent research indicates that oxidative stress plays a significant role in the development of endometriosis. The present administration of progestin hormone treatment has been shown to induce additional oxidative stress, which is characterized by elevated levels of oxidative stress indicators, including malondialdehyde (MDA), and a reduction in the enzymatic antioxidant superoxide dismutase (SOD). The presence of hormonal imbalances in conjunction with these alterations fosters an environment conducive to the metastasis of endometrial cells. This process initiates inflammatory pathways, angiogenesis, and the formation of lesions and tumors, ultimately exacerbating the state of endometriosis. Research findings indicate that propolis has inherent antioxidant properties, characterized by a high concentration of flavonoid components and phenolic acids. Propolis contains active compounds that have the ability to trap free radicals by forming more stable molecules. Propolis has anti-inflammatory, antimicrobial, and immunomodulatory characteristics, hence potentially enhancing the patient's oxidative stress state, mitigating morbidity, and reducing the duration of hospitalization. This research aims to assess the possible impact of flavonoids found in propolis on the treatment of endometriosis.